Investments in green strategies improve company value - Kok, Adeline Li Ming * (2012)
The opportunities and challenges in investing in environmental strategies have become an important issue as the world transcends into being more sustainable. Investments in green related strategies are given more importance as there is now opportunity to develop and engage in green projects. Firms are beginning to engage and involved themselves in the green marketplace at rapid pace to keep themselves on par with customers’ expectation as well as society’s expectation. These expectations include the demands for the reduction of ecological effects and the potential benefits of such actions. There has to be some sort of quantifiable meaning to these environmental actions to firms while trying to meet customers’ and societal expectations. Thus, the question of whether firms that invest in green initiatives improve their company value arises.